Gambaran Kebiasaan Merokok Anggota Keluarga Pada Kejadian Infeksi Saluran Pernafasan Akut (ISPA) Balita Di Puskesmas Putri Ayu - Nanda Poniar; Nurhusna Nurhusna; Yulia Indah Permata Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Acute Respiratory Infection (ARI) is an acute infection involving the organs of the upper respiratory tract and lower respiratory tract. Lack of parental knowledge about the dangers of cigarette smoke that can trigger the incidence of ARI in toddlers.This type of research uses a quantitative correlation design. This research was conducted at the Putri Ayu Health Center, Jambi City. The population of respondents with a sample size of 160 respondents using purposive sampling technique. Based on the results of research conducted by researchers, most of the toddlers who suffer from ARI aged <10 months as many as 37 people (23.12%), have a female gender of 83 toddlers with ARI, and the incidence of ARI associated with toddlers and smoking habits of family members in the house as many as 143 toddlers (89.38%) affected by ARI. Results of this study are expected to provide information about the dangers of cigarette smoke, especially for children, so that the family can change their smoking habit.